ANALYSIS OF FACTORS AFFECTING CONSUMER SATISFACTION ON YAMAHA NMAX MOTORCYCLES (STUDENT CASE STUDY STIE-INDRAGIRI) - Hermanto, Hermanto; Heriasman, Heriasman (AGUSPATI Research Institute, 2021)
This research was conducted on Sekolah Tinggi Ilmu Ekonomi Indragiri Rengat especially students who use Yamaha NMAX motorcycles. The purpose of this study was to determine the factors that influence consumer satisfaction on NMAX motorcycles (student case study/I STIE – Indragiri Rengat). With the number of samples used as many as 145 respondents. Sampling method using the census method. Data processing using the IBM SPSS Statistic 21 program. The results of the study can be concluded that: (1) The product partially has a significant effect on Consumer Satisfaction on NMAX Motorcycles (Case Study of Students/I STIE – Indragiri). (2) Price partially has a significant effect on Consumer Satisfaction on NMAX Motorcycles (Case Study of Students/I STIE – Indragiri). (3) Product and Price simultaneously have a significant effect on Consumer Satisfaction on NMAX Motorcycles (Case Study of Students/I STIE – Indragiri).